Literature Review on the Discrete Element Method in Asphalt Mixtures - Yao, Hui; Xu, Mei; Liu, Junfu; Liu, Yu; Ji, Jie; You, Zhanping (Frontiers in Materials, 2022)
Asphalt mixtures are commonly used in pavement engineering, especially for highway construction. The mechanism exploration and analysis of pavement distress are the main challenges for researchers and industry managers. Thereby, it is important to understand their properties and interaction mechanisms in asphalt mixtures. It is difficult to conduct some sophisticated or microscale tests in the laboratory, and numerical simulation and virtual tests can be solutions for these cases with low costs. The Discrete Element Method (DEM) is a promising tool for researchers to undertake these tasks. This paper mainly summarized and analyzed the research progress and development prospect of DEMs in asphalt mixtures from a series of technical sections. The laboratory test results were often used to calibrate the DEM simulations as well as Two-dimensional (2D) and Three-dimensional (3D) modeling. Several modeling methods were developed to generate digital samples, like user-defined, image-based, random-modeling. In addition, the conclusions can be referenced by researchers for the development of numerical simulations.